The Relationship Between Inpartu Mothers' Anxiety Regarding Guidance on Delivery and the Incidence of Perineal Rupture at OBI Hospital, South Halmahera - Kartini Karim; Reny Retnaningsih (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Anxiety in laboring mothers is a psychological factor that can influence the course of labor, particularly during the second stage, and increase the risk of complications such as perineal rupture. Along with obstetric factors, the quality of labor guidance is crucial in preventing perineal trauma. This study aimed to analyze the relationship between maternal anxiety, labor guidance, and the incidence of perineal rupture at Obi Hospital, South Halmahera. Using an observational analytical design with a cross-sectional approach, the study involved 50 laboring mothers undergoing vaginal delivery, selected through purposive sampling. Data collection took place from February to April 2024, with maternal anxiety measured using a standardized anxiety questionnaire. Labor guidance and perineal rupture were assessed through observation sheets and clinical examinations. Data analysis was conducted univariately and bivariately using the Chi-Square test with a significance level of p < 0.05. The results showed a significant relationship between maternal anxiety and labor guidance (p < 0.05), as well as between maternal anxiety and perineal rupture (p < 0.05). Additionally, labor guidance was significantly associated with the incidence of perineal rupture (p < 0.05). Mothers with higher anxiety levels tended to receive poor labor guidance and had a higher risk of perineal rupture. The study concludes that maternal anxiety significantly impacts labor guidance and perineal rupture, emphasizing the need for holistic care that addresses both psychological and physical aspects of childbirth.